A Large Family of AvrLm6-like Genes in the Apple and Pear Scab Pathogens, Venturia inaequalis and Venturia pirina - Shiller, Jason; Van de Wouw, Angela P.; Taranto, Adam P.; Bowen, Joanna K.; Dubois, David; Robinson, Andrew; Deng, Cecilia H.; Plummer, Kim M. (Frontiers in Plant Science, 2015)
Venturia inaequalis and V. pirina are Dothideomycete fungi that cause apple scab and pear scab disease respectively. Whole genome sequencing of V. inaequalis and V. pirina isolates has revealed predicted proteins with sequence similarity to AvrLm6, a Leptosphaeria maculans effector that triggers a resistance response in Brassica napus and Brassica juncea carrying the resistance gene, Rlm6. AvrLm6-like genes are present as large families (> 16 members) in all sequenced strains of V. inaequalis and V. pirina, while in L. maculans, only AvrLm6 and a single paralogue have been identified. The Venturia AvrLm6-like genes are located in gene poor regions of the genomes, and mostly in close proximity to transposable elements which may explain the expansion of these gene families. An AvrLm6-like gene from V. inaequalis with the highest sequence identity to AvrLm6 was unable to trigger a resistance response in Rlm6 carrying Brassica juncea. RNA-seq and qRT-PCR gene expression analyses, of in planta and in vitro grown V. inaequalis, has revealed that many of the AvrLm6-like genes are expressed during infection. An AvrLm6 homologue from V. inaequalis that is up-regulated during infection was shown (using a YFP-fusion protein construct) to be localized to the sub-cuticular stroma during infection of apple hypocotyls.